Analisis Kinerja Keuangan: Peran Kepemilikan Institutional Dan Fin-Tech Pada Perusahaan Asuransi Jiwa Konvensional - Syifa Maharani Irianto; Hayuningtyas Pramesti Dewi (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2026)
The purpose of this study is to investigate factors that can influence financial performance, namely institutional ownership and financial technology. Data were obtained from the Financial Services Authority (OJK), specifically the annual reports of conventional life insurance companies, and tested using multiple linear regression analysis. The results indicate that institutional ownership and financial technology have a positive effect on financial performance.